Analyzing Lexical Resource in the Speaking Skill of Street Vendors in Tourism Area - Muhammad Junaidi Marzuki; Hamzani Wathoni; Muhammad Anan Abdullah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
This study investigates the lexical resources utilized by street vendors in a popular tourism area and their impact on effective communication with international tourists. Through qualitative analysis of speech samples from a diverse group of vendors, the research identifies common vocabulary patterns, the extent of lexical diversity, and the use of language adaptation strategies such as code-switching and simplification. The findings reveal that while vendors often rely on a limited vocabulary, they effectively use context-specific terms and non-verbal cues to enhance mutual understanding. Additionally, the study highlights the challenges faced by vendors due to language barriers and suggests potential language training programs to improve their communicative competence. This research underscores the importance of targeted lexical resource development to boost vendors' speaking skills, ultimately contributing to better customer interactions and increased economic opportunities in the tourism sector. Keyword: Lexical Resource; Speaking Skill; Street Vendors; Tourism Area.